PENGANTAR POLITIK ISLAM DAN ISLAM POLITIK - Istadiyantha Istadiyantha (Arabic Literature Department, 2014)
Politic has been defined simply by Harold Laswell as who gets what, when, how?Many people say that politic is synonymous with power. The